Analysis of Public Service Innovation Based on JAKI Application in Realizing the New Public Service - Riani, Ni Wayan; Wijaya, Komang Adi Sastra; Yudartha, I Putu Dharmanu; Savitri, Renny (Brawijaya University, 2024)
The existence of technology is positive side for the government in managing public services to create services that are effective, efficient, transparent and able to involve the community. The implementation of new public services in local government is manifested by public service innovations that utilize technology. One application is the JAKI application which is used as a public service application in DKI Jakarta Province. This research uses qualitative research with an exploratory approach. Viewed from the perspective of the new public service, it has met the indicators; serve citizens, not customers; seek the public interest; value citizenship over entrepreneurship; recognize that accountability isn't simple; serve rather than steer; value people, not just productivity. In realizing the new public service in the JAKI application based public service, several problems were encountered. In this case, the government needs to pay more attention to strategic steps in popularizing the JAKI application.